2016
DOI: 10.1136/thoraxjnl-2015-207429
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of a potent PI3 kinase/mTOR inhibitor as a novel anti-fibrotic agent in IPF

Abstract: RationaleIdiopathic pulmonary fibrosis (IPF) is the most rapidly progressive and fatal of all fibrotic conditions with no curative therapies. Common pathomechanisms between IPF and cancer are increasingly recognised, including dysfunctional pan-PI3 kinase (PI3K) signalling as a driver of aberrant proliferative responses. GSK2126458 is a novel, potent, PI3K/mammalian target of rapamycin (mTOR) inhibitor which has recently completed phase I trials in the oncology setting. Our aim was to establish a scientific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 39 publications
4
133
1
Order By: Relevance
“…Using a murine model, Chung et al (22) demonstrated that rapamycin treatment reduced inflammatory cytokine expression, extracellular matrix production and senescence in type II pneumocytes, and that rapamycin protected against radiation-induced pulmonary fibrosis. Phosphoinositide 3-kinase (PI3K) was reported as a promising therapeutic target for idiopathic pulmonary fibrosis (23). Rapamycin may increase connective tissue growth factor expression in lung fibroblasts by regulating the PI3K signaling pathway (24).…”
Section: Discussionmentioning
confidence: 99%
“…Using a murine model, Chung et al (22) demonstrated that rapamycin treatment reduced inflammatory cytokine expression, extracellular matrix production and senescence in type II pneumocytes, and that rapamycin protected against radiation-induced pulmonary fibrosis. Phosphoinositide 3-kinase (PI3K) was reported as a promising therapeutic target for idiopathic pulmonary fibrosis (23). Rapamycin may increase connective tissue growth factor expression in lung fibroblasts by regulating the PI3K signaling pathway (24).…”
Section: Discussionmentioning
confidence: 99%
“…The use of pan-PI3 kinase (PI3K)/mammalian target of rapamycin (mTOR) in IPF is an example of the potential role of existing oncology drugs as novel therapeutic agents in IPF patients. GSK2126458 inhibited PI3K signalling and functional responses in IPF-derived lung fibroblasts, through blocking Akt phosphorylation in cells derived from tissue and BAL of IPF patients [119]. A double-blind, placebo-controlled, parallel study of GSK2126458, a PI3K/mTOR inhibitor, has been completed (NCT01725139, waiting for results).…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Mercer et al 13 propose the novel antitumour agent GSK2126458, a pan-class I phosphoinositide 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) inhibitor, as a therapeutic agent for IPF. Following activation via tyrosine kinases and/or G protein-coupled receptors, PI3Ks generate the lipid second messenger phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P 3 ), which coordinates localisation of multiple signalling molecules with a Pleckstrin homology domain, most importantly Akt, at the plasma membrane 14.…”
mentioning
confidence: 99%
“…The integration of these two data sets, the PK data from the ongoing trial and the gathered in vitro data using the described functional readouts, is a major strength of this study as it allowed the authors to deduce a dosing framework, which should ensure safe and effective target engagement in the lungs of patients with IPF. Hereby, Mercer et al 13 not only paved the way for an IPF proof-of-mechanism study (NCT01725139), but provided a generally valid roadmap for how to evaluate the potential of drug repositioning at the early clinical trial stage, and the authors should be lauded for this effort.…”
mentioning
confidence: 99%
See 1 more Smart Citation